PENERAPAN STRATEGI PREDICTION GUIDE UNTUK MENINGKATKAN PEMAHAMAN BELAJAR SISWA PADA MATA PELAJARAN PAI - yanti, indisri ninda; Nahwiyah, Sopiatun; Mailani, Ikrima (J-PAI: Jurnal Pendidikan Agama Islam, 2018)
Abu Bakar Yunus stated that the main task of a teacher is to create a conducive and pleasant learning atmosphere or climate that makes students understand the material being taught. But based on the results of observations there are several symptoms that the researchers did, namely: Many students who are unable to answer the questions posed by the teacher, students are not able to redefine the material taught by the teacher, students are not able to translate the verses of the Qur'an relating to PAI subject matter, students are less able to explain the material taught in their own language and there are still many students who have not yet reached KKM (Minimum Accuracy Criteria) To overcome this problem, the researcher found a suitable strategy to be applied in PAI learning namely prediction guide strategy (guess the lesson) . The prediction guide strategy is a learning strategy that emphasizes students to guess or predict the material to be delivered by the teacher. The aim of the researchers to conduct classroom action research was to improve students' understanding of learning by applying a prediction guide strategy (guessing lessons) in Class VII PAI subjects at Singingi Middle School 6. Data collection techniques are carried out by tests, observations, interviews and documentation. The application of the prediction guide strategy can improve the learning comprehension of Grade VII students in PAI subjects at Singingi Middle School 6. This is evident from the pre-cycle only students who have a learning understanding of only 22.2%, the first cycle rises to 35.5%, the second cycle rises to 55.4% and it turns out that in the third cycle 82.2% of students have a good understanding of learning in PAI learning.Keywords: Prediction Guide Strategy; Learning Understanding; PAI